Is There Any Mosaicism in REarranged During Transfection Variant in Hirschsprung Disease’s Patients? - Iskandar, Kristy; Simanjaya, Susan; Indrawan, Taufik; Kalim, Alvin Santoso; Marcellus,; Heriyanto, Didik Setyo; Gunadi, (Frontiers in Pediatrics, 2022)
Background Hirschsprung disease (HSCR) is a heterogeneous genetic disease characterized by the absence of ganglion cells in the intestinal tract. The REarranged during Transfection (RET) is the most responsible gene for its pathogenesis. RET’s somatic mosaicisms have been reported for HSCR; however, they are still under-recognized. Therefore, we determined the frequency of somatic mutation of RET rs2435357 in HSCR patients at our institution. Methods We performed RET rs2435357 genotyping from 73 HSCR formalin-fixed and paraffin-embedded (FFPE) rectal and 60 non-HSCR controls using the PCR-RFLP method. Subsequently, we compared those frequencies of genotypes for RET rs2435357 with our previous genotyping data from 93 HSCR blood specimens. Results The frequencies of genotypes for RET rs2435357 in HSCR paraffin-embedded rectal were CC 0, CT 11 (15%), and TT 62 (85%), whereas their frequencies in HSCR blood samples were CC 4 (4.3%), CT 22 (23.7%), and TT 67 (72%). Those frequencies differences almost reached a significant level (p = 0.06). Moreover, the frequency of RET rs2435357 risk allele (T) was significantly higher in HSCR patients (135/146, 92.5%) than controls (46/120, 38.3%) (p = 3.4 × 10–22), with an odds ratio of 19.74 (95% confidence interval = 9.65–40.41). Conclusion Our study suggests somatic mosaicism in HSCR patients. These findings further imply the complexity of the pathogenesis of HSCR. Moreover, our study confirms the RET rs2435357 as a significant genetic risk factor for HSCR patients.